1987
DOI: 10.1111/j.1574-6968.1987.tb02619.x
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of the fucose-binding lectin ofPseudomonas aeruginosa

Abstract: PA‐II lectin of Pseudomonas aeruginosa, purified by affinity chromatography, was examined for its relative affinity to various carbohydrates using equilibrium dialysis and hemagglutination inhibition tests. This lectin was found to exhibit a high affinity for L‐fucose and its derivatives. Among them, p‐nitrophentl‐α‐L‐fucose was the strongest inhibitor, followed by L‐fucose →L‐fucosylamine L‐galactose →D‐mannose →?→D‐fructose. The association constant (Ka) of L‐focuse for PA‐II was 1.5 × 106· M−1 and the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 9 publications
0
27
1
Order By: Relevance
“…The localization of LecB in the outer membrane of P. aeruginosa and its high affinity for L-fucose and its derivatives, like pNPF (Garber et al, 1987), suggested that this lectin might be bound to the outer membrane via fucose-containing structures. This assumption was tested by incubating an isolated outer-membrane fraction with 20 mM of either pNPF or D-galactose, which served as a negative control because the affinity of LecB for D-galactose is extremely low (Garber et al, 1987).…”
Section: Lecb Binds To Carbohydrate Ligands In the Outer Membranementioning
confidence: 99%
See 1 more Smart Citation
“…The localization of LecB in the outer membrane of P. aeruginosa and its high affinity for L-fucose and its derivatives, like pNPF (Garber et al, 1987), suggested that this lectin might be bound to the outer membrane via fucose-containing structures. This assumption was tested by incubating an isolated outer-membrane fraction with 20 mM of either pNPF or D-galactose, which served as a negative control because the affinity of LecB for D-galactose is extremely low (Garber et al, 1987).…”
Section: Lecb Binds To Carbohydrate Ligands In the Outer Membranementioning
confidence: 99%
“…It consists of four 12?75 kDa subunits (Gilboa-Garber, 1972;Avichezer et al, 1992) and has been shown to cause cytotoxic effects on respiratory epithelial cells by decreasing their growth rate, thus contributing to respiratory epithelial injury during P. aeruginosa infection (Bajolet-Laudinat et al, 1994). In addition, it was demonstrated that LecA induces a permeability defect in the intestinal epithelium, resulting in increased absorption of exotoxin A, an important extracellular virulence factor of P. aeruginosa (Laughlin et al, 2000).LecB consists of four 11?73 kDa subunits, each exhibiting a high specificity for L-fucose and its derivatives (GilboaGarber et al, 2000;Garber et al, 1987) and also for Dmannose, with lower affinity. Its crystal structure was determined recently (Mitchell et al, 2002(Mitchell et al, , 2005Loris et al, 2003).…”
mentioning
confidence: 99%
“…solanacearum possesses a PA-IIL-like lectin (RS-IIL), but does not produce a PA-IL-like one (Gilboa-Garber et al, 2000;Sudakevitz et al, 2004). RS-IIL, which is shorter than PA-IIL by one amino acid (11?60 kDa), resembles it in its composition, Ca 2+ requirement for activity and a very high sugar affinity (Garber et al, 1987;Sudakevitz et al, 2004). However, it differs from PA-IIL in showing highest affinity to mannose, accompanied by a lower avidity for fucose and related sugars (Sudakevitz et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…aeruginosa produces PA-IIL (11?73 kDa) (Gilboa-Garber, 1982;Garber et al, 1987) in addition to a galactophilic lectin, PA-IL (12?76 kDa) (Gilboa-Garber, 1972). Both lectins are composed of four identical subunits (Mitchell et al, 2002;Ciocci et al, 2003;Imberty et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Pseudomonas aeruginosa, the matrix protein CdrA is both cell associated and secreted and likely promotes cell-matrix and matrix-matrix interactions by binding to the Psl polysaccharide (8), which itself is cell associated and secreted (9). Additionally, the lectins LecA, specific for D-galactose (10), and LecB, specific for L-fucose (11), are thought to promote cell-cell interactions (12) during P. aeruginosa biofilm formation.…”
mentioning
confidence: 99%